Persepsi Masyarakat Nagari Kasang terhadap Pengadaan Tanah Pembangunan Jalan Tol Padang Pekanbaru (Padang-Sicincin) - Andra Fahmi; Nora Eka Putri (PUBLICNESS: Journal of Public Administration studies, 2022)
From the field review, this study aims to determine the opinion of Kasang Nagari residents on land acquisition for the construction of the Padang-Pekanbaru (Padang-Sicincin) Toll Road. This analysis is the background of the intensity of policy makers in providing this land properly so that no party feels betrayed, especially residents. However, the application for land acquisition in Nagari Kasang is still in the form of the low price offered by the government to the residents, the unsuccessful negotiation of land prices by the policy authorities with the community, and residents whose lands have been evicted. in danger of running out of livelihood. This research is qualitative with descriptive procedures that have been carried out in Nagari Kasang, Padang Pariaman Regency, which was attacked in the construction of the Padang-Pekanbaru toll road (the Padang-Sicincin section). The results of this study indicate that the residents' assumptions have been accepted and interpreted well, land acquisition has been attempted in a structured manner, and compensation for land losses has been explained to residents